Exploring new strategies in diseases resistance of horticultural crops - Xu, Jun; Zhang, Ningyuan; Wang, Ke; Xian, Qianqian; Dong, Jingping; Chen, Xuehao (Frontiers in Sustainable Food Systems, 2022)
Horticultural crops are widely threatened and damaged by different biotic stresses caused by bacteria, fungi, oomycetes, viruses and root-knot nematodes, which not only limit their growth and development, yield and quality, but also affect their adaptability and geographic distribution. Especially, the continuous cropping model in the horticultural facilities causes the soil-borne diseases to occur frequently, and severely restricts the high-yield, high-quality and high productivity Recent progress in the understanding of mechanisms that confer tolerance to different diseases through innovative strategies including host-induced gene silencing (HIGS), targeting susceptibility genes, and rootstocks grafting applications were reviewed to systematically explore the resistance mechanisms against horticultural plant diseases. Coming work should successfully breed resistant varieties using these strategies combined with molecular biologic methods.